HUBUNGAN ANTARA SELF EFFICACY DENGAN PROKRASTINASI AKADEMIK MAHASISWA PROGRAM STUDI PG PAUD FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Chairilsyah, Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack: The aim of this research is to know whether there is any correlation between students’ self efficacy and academic procrastination in education program of Teacher Education Courses for Early Childhood Education and Faculty of Teacher Training and Education at University of Riau year 2012. The population of this research is the students of Teacher Education Courses for Early Childhood Education in Faculty of Teacher Training at University of Riau year 2012 that consists of 112 students, the samples of this research are 53 students which taken by using slovin formula. Method of this research is quantitative correlation to know the correation between independent variable and dependent variable. The technique of collecting data used quistioner in Likert scale form. The technique of analyzing data used scale test and statistic analitical by using SPSS program for Windows Ver.20. Based on the hypothesis there is any significant negative correlation between sudents’ self efficacy and academic procrastination in Teacher Education Courses for Early Childhood Education Faculty of Teacher Training and Education at University of Riau year 2012. It could be seen from the result of correlation cooficient that rxy = -0,432 and significant level is 0,001 < 0,05. The correlation between students’ self efficacy and academic procrastination is in the medium level which is the KP = r² x 100% = 18,66%, it means that self efficacy affect the academic procrastination as much as 18,66%. Key Words: Self Efficacy, Academic Procrastination